The Cardioprotective Effects of Irbesartan and Candesartan in Isoproterenol Induced Cardiomyopathy in Rats (Global Journal of Medical Research, 2014)
The presence of a wide selection of angiotensin receptor blockers and the conflicting evidence regarding their cardioprotective effect, led to the attempt to evaluate the impact of irbesartan and candesartan on cardiac hypertrophy and remodeling. Female Albino rats were divided into 3 groups. The first group served as the control group and was given 1 ml distilled water via oral gavage and 0.5 ml distilled water subcutaneously. The second group was the isoproterenol (ISO) group and was given a daily S.C. injection of ISO at a dose of 5 mg/kg. The third group served as the treatment group and it was subdivided into 2 groups, both received ISO as stated previously along with a treatment drug which was administered via oral gavage and they included: ISO-Irb(irbesartan 50 mg/kg/day), and ISO-Cand(candesartan 2.6 mg/kg/day). All groups were treated for a period of 14 days. The assayed parameters included; mean serum Matrix metalloproteinase 9 (MMP-9), Cardiac troponin I (cTn-I), and Heart weight to Body weight (Hw/Bw) ratio.
Keywords: angiotensin; isoproterenol; cardiomyopathy; ARBs; MMP-9; cTn-i; candesartan; irbesartan